PROGNOSIS OF MECHANICAL STABILITY OF STRUCTURAL PARTICLEBOARDS BASED ON MODIFIED PHENOL-FORMALDEHYDE RESINS DURING LONG-LASTING STAY IN THE OPEN IN REAL CLIMATIC CONDITIONS (Innovation in Woodworking Industry and Engineering design, 2026)
Mechanical stability – relative reduction of modulus of elasticity and stiffness in bending, of structural particleboards (SPBs) based on modified phenol-formaldehyde resins (PFRs) during long-lasting stay in the open in natural climatic conditions has been determined experimentally. The impact of atmospheric effects by varying climatic factors, such as heating, wetting, freezing, insolation, etc., on strain-strength characteristic of SPBs has been established under field conditions. To assess the mechanical stability of SPBs during long-lasting stay in the open in natural climatic conditions, respective algorithms and a diagram have been proposed. The traditionally used %, and for the stiffness – %, at a board thickness of 18 ± 2 mm, have been adopted as permissible rate of reduction of the relative modulus of elasticity. SPBs based on PFR modified with aluminium sulphate, in which % for a 10-year period of exposure in the open has been attained, have shown relatively highest weather resistance. For the boards based on PFR and aluminium sulphate, % for a 5-year period of stay in the open, but with respect to stiffness, the permissible duration of exposure is considerably lower – under 1.5 years.